S-doped CQDs tailored transparent counter electrodes for high-efficiency bifacial dye-sensitized solar cells. (20th January 2018) - Zhang, Yue; Zhao, Yuanyuan; Duan, Jialong; Tang, Qunwei
Abstract: Bifacial photovoltaics are promising devices for significantly harvesting solar energy and generating power from either front or rear side. We present here the fabrication of new category of high-performance bifacial dye-sensitized solar cells (DSSCs) tailored with transparent S-doped carbon quantum dots (S-CQDs)/metal selenide counter electrodes. Arising from photoexcitation of S-CQDs and therefore increased electron density at electrode surfaces, the catalytic ability of S-CQDs tailored counter electrodes is markedly enhanced under solar irradiation. The bifacial DSSCs yield maximized front and rear efficiencies of 9.15% and 6.26%, respectively. Highlights: S-CQDs tailored metal selenide CEs are made for bifacial DSSCs. The S-CQDs tailored CEs have higher catalytic activity under solar irradiation. The bifacial DSSCs yield front and rear efficiencies of 9.15% and 6.26%, respectively.